Analisis Dan Implementasi Jaringan Komputer Brembuk.Net Sebagai RT/RW.Net Untuk Mendukung E-Commerce Pada Desa Masbagik Utara - Ahmad Tantoni; Maulana Ashari; Mohammad Taufan Asri Zaen (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2020)
One of the districts that is the central of the economy is Masbagik. The population working in the trading sector as traders in Masbagik Utara Village is almost 70%. Along with the times, buying and selling activities are not only have been done conventionally, but also through e-Commerce. E-Commerce must be supported by adequate information technology infrastructure, namely internet connection in its business processes. Based on observations in the Masbagik Utara Village, businesses using internet connections from well-known ISPs in their business activities, and this is considered to be less economical in the e-Commerce activities. Therefore, research is conducted to analyze, design and implement rt / rw.net by giving the wifi network name "brembuk.net" which is expected to help provide a choice of solutions related to internet connection that will be used by e-Commerce businesses in Masbagik Utara village. The research uses PPDIOO method (Prepare, Plan, Design, Implement, Operate, Optimize). The implementation of the brembuk.net computer network as rt / rw.net to support e-Commerce is one of the way to access cheap and stable internet and unlimited quota to access the internet in doing business for online businesses in Masbagik Utara village.